Trust in distance learning during the COVID-19 pandemic: Evaluation of the quality of education of students and teachers of Russian universities - A. G. Tyurikov; D. A. Kunizheva; E. V. Frolova; O. V. Rogach (Образование и наука)
Introduction. The widespread transition of higher education institutions to distance learning during the COVID-19 pandemic contributed to a decrease in education quality ratings. These trends, against the background of forecasts of an increase in the share of “distance learning” in the educational process, may initiate an increase in social tension, as well as a decrease in the level of trust in the activities of authorities that do not fully ensure the maintenance of the quality of education in the new conditions.Aim. The aim of the article was to assess the quality of education in the context of distance learning, to analyse the consequences of the transformation of the practices of interaction between a teacher and a student.Methodology and research methods. An all-Russian comprehensive sociological study was conducted using the following methods: questionnaires and focus groups. The first wave of the study was a survey of students of higher educational institutions of economic orientation from 14 regions of the Russian Federation (the sample population was 6,500 students). During the second wave, the following projects were implemented: 1) a survey of students of economic universities from 17 regions of the Russian Federation (sample population = 7600); 2) a survey of teachers of the Financial University (sample population = 520); 3) focus groups with students.Results and scientific novelty. The results obtained allow the authors to draw the following conclusions: the remote format of classes during the quarantine restrictions did not cause a sharp drop in the quality of education. Meanwhile, students’ preferences demonstrate a commitment to the traditional form of education. The factors that shape the readiness of students for distance education (course of study, budget/contract form, direction of training) are identified. The main problem is related to the lack of face-to-face communication, which is interpreted by the authors not so much as an objective limitation of the remote format of work, but as a subjective unavailability, low adaptation of pedagogical and communicative practices to remote online interaction. The study showed the strengthening of the role of informal network interactions that ensure the filling of the information vacuum in conditions of uncertainty, the formation of trustPractical significance. The research results and conclusions can be used for further theoretical and practical developments in this area, and can also become the basis for the preparation of methodological recommendations to reduce the negative consequences of the introduction of distance learning and improve the quality of education in the new environment.